The Effect of Isoflurane and Ketamine/Xylazine on Epileptiform Activity in Genetic Absence Epilepsy (Wag/Rij) Rats Model - Algailani, Lubna Adil Kamil; Al Kaleel, Ali Zaher Kamel; Arslan, Gokhan; Ayyıldız, Mustafa; Agar, Erdal (Wiley, 2019)
…
Keywords: Epilepsy; Wag\Rij; Isoflurane; Ketamine; Xylazine; Rat